5x + 6 = 1
Subtract 6 from both sides.
5x = -5
Divide from both sides.
x = -1 (ANSWER)
hope this helps!!
Answer:
B will be the answer...
Step-by-step explanation:
The second equation in system B is only in terms of y, so we need to use elimination to eliminate the x term from the second equation in system A.
To do that, we need to multiply the first equation by 5.
5 (-x − 2y = 7)
-5x − 10y = 35
Add to the second equation. Notice the x terms cancel out.
(-5x − 10y) + (5x − 6y) = 35 + (-3)
-16y = 32
Combining this new equation with the first equation from system A will get us system B.
-x − 2y = 7
-16y = 32
The first option is greater.
Answer: 2x-1
combine like terms: 4x and -2x
-4 and 3